Differentiation therapy in poor risk myeloid malignancies: Results of companion phase II studies. (October 2016) - Norsworthy, Kelly J.; Cho, Eunpi; Arora, Jyoti; Kowalski, Jeanne; Tsai, Hua-Ling; Warlick, Erica; Showel, Margaret; Pratz, Keith W.; Sutherland, Lesley A.; Gore, Steven D.; Ferguson, Anna; Sakoian, Sarah; et al.
Highlights: Myeloid growth factors enhance the leukemic activity of differentiation agents in vitro . GM-CSF plus either bexarotene or entinostat demonstrated differentiation activity in heavily pretreated AML and MDS. GM-CSF in combination with either bexarotene or entinostat has an acceptable toxicity profile in previously treated AML and MDS. Abstract: Pre-clinical data in non-M3 AML supports the use of differentiation therapy, but clinical activity has been limited. Myeloid growth factors can enhance anti-leukemic activity of differentiating agents in vitro . We conducted companion phase II trials investigating sargramostim (GM-CSF) 125 μg/m 2 /day plus 1) bexarotene (BEX) 300 mg/m 2 /day or 2) entinostat (ENT) 4–8 mg/m 2 /week in patients with MDS or relapsed/refractory AML. Primary endpoints were response after at least two treatment cycles and toxicity. 26 patients enrolled on the BEX trial had a median of 2 prior treatments and 24 enrolled on the ENT trial had a median of 1. Of 13 response-evaluable patients treated with BEX, the best response noted was hematologic improvement in neutrophils (HI-N) seen in 4 (31%) patients; none achieved complete (CR) or partial remission (PR). Of 10 treated with ENT, there was 1 (10%) partial remission (PR) and 2 (20%) with HI-N. The secondary endpoint responses of HI-N with each combination were accompanied by a numerical increase in ANC (BEX: 524 to 931 cells/mm 3, p = 0.096; ENT: 578 to 1 137 cells/mm 3, p = 0.15) without increasing marrow blasts. Shared grade 3–4 non-hematologic toxicities included febrile neutropenia, bone pain, fatigue, and dyspnea. GM-CSF plus either BEX or ENT are well tolerated in resistant and refractory MDS and AML and showed modest clinical and biologic activity, most commonly HI-N.